CEPHEID PULSATIONS FROM RADIAL VELOCITY MEASUREMENTS - Gorynya, N. A.; Samus, N. N. (Одеські астрономічні публікації, 2017)
We discuss the results of our many-year program of Cepheid radial velocities concerning the Hertzsprung sequence in radial-velocity curves, double-mode Cepheids, the period-radius relation, binary Cepheids.